Towards a critical pedagogy for inclusion: disability-led arts and its radical promise in Singapore - Zhuang, Victor Kuansong (2024)
The inclusion of disabled people in Singapore (and globally) is gaining traction given the dominance of transnational instruments like the United Nations Convention on the Rights for Persons with Disabilities. Yet, in the absence of disability rights legislation, inclusion in Singapore has taken on markedly different forms, based on ablenationalist notions of productivity and meritocracy. Situated amidst these global and national frameworks of social inclusion, we consider the recent emergence of disability-led arts in Singapore. These disabled-led initiatives have proliferated in the past five years and have afforded new opportunities to challenge existing meanings of inclusion and to impart new forms of knowledge about the disabled body. In this article, we analyse recent disabled-led art productions put up by Access Path Productions, a disability-led arts creative organisation. In pivoting to the disabled body/mind as a generative form of knowledge and embodiment, these disabled-led performances offer new artistic practices spanning both digital and physical forms. Importantly, these initiatives have engaged with existing art and cultural spaces and institutions in Singapore, transforming existing ways of doing, thinking, and knowing about disability and offering a critical praxis aimed at (re)educating the public on the meanings of disability.